Why William Shakespeare Did Not Write the Works Attributed to Him, and Why Sir Henry Neville Did - Rubinstein, William (Journal of Scientific Exploration, 2024)
This article complements those published in the special issue of this Journal (Summer 2023) about the Shakespeare Authorship Question. After making some important points about why William Shakespeare could not have written the works attributed to him, the present paper argues the case for Sir Henry Neville (1563–1615) as the real author. Of particular interest is the fact that Neville’s handwriting, in letters and in annotations in books, appears to be identical with the handwriting in “Hand D” of the play Sir Thomas More, the only manuscript source believed to be in the handwriting of “William Shakespeare”. Twelve key points are then advanced as to why Neville was the real author of Shakespeare’s works.